The Role of Motivation in Mediating Work Design and Organizational Culture on Village Apparatus Performance - Marlina Kusumawati; Jefri Heridiansyah; Theresia Susetyarsi; Sri Wiranti Setiyanti; Prabowo, Catur (Universitas Negeri Semarang, 2024)
The research objective is to analyze the effect of work design, organizational culture and work motivation on the performance of village officials; analyze the effect of work design and organizational culture on work motivation; analyze the effect of work design on the performance of village apparatus through work motivation; analyze the effect of organizational culture on the performance of village apparatus through work motivation. The population of this study were all village officials in the Wirosari District, Grobogan Regency, with BUMDES management activities not running, namely 63 village officials from a number of 9 villages. The sampling technique uses a saturated sample. Therefore, the number of samples taken was also 63 village officials. Data analysis techniques using smartpls. The results of the study found that all hypotheses had a positive and significant direct effect, except for work design on facilitator performance. In the mediation hypothesis, work motivation is able to mediate the influence of work design and the performance of village apparatus, but is unable to mediate the influence of organizational culture and the performance of village apparatus.